2021
DOI: 10.3389/fneur.2021.701170
|View full text |Cite
|
Sign up to set email alerts
|

1H Magnetic Resonance Spectroscopy to Understand the Biological Basis of ALS, Diagnose Patients Earlier, and Monitor Disease Progression

Abstract: At present, limited biomarkers exist to reliably understand, diagnose, and monitor the progression of amyotrophic lateral sclerosis (ALS), a fatal neurological disease characterized by motor neuron death. Standard MRI technology can only be used to exclude a diagnosis of ALS, but 1H-MRS technology, which measures neurochemical composition, may provide the unique ability to reveal biomarkers that are specific to ALS and sensitive enough to diagnose patients at early stages in disease progression. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 91 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…A glutamate/GABA imbalance and hyperexcitability has been hypothesized as the cause of ALS. Several studies have investigated these neurotransmitters using magnetic resonance spectroscopy with some evidence for elevated glutamate and decreased GABA levels, suggesting a piece in the puzzle of neuronal excitability in ALS (29)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A glutamate/GABA imbalance and hyperexcitability has been hypothesized as the cause of ALS. Several studies have investigated these neurotransmitters using magnetic resonance spectroscopy with some evidence for elevated glutamate and decreased GABA levels, suggesting a piece in the puzzle of neuronal excitability in ALS (29)…”
Section: Discussionmentioning
confidence: 99%
“…A glutamate/GABA imbalance and hyperexcitability has been hypothesized as the cause of ALS. Several studies have investigated these neurotransmitters using magnetic resonance spectroscopy with some evidence for elevated glutamate and decreased GABA levels, suggesting a piece in the puzzle of neuronal excitability in ALS (29) To further understand the interaction of ALS on the beta frequencies in our data we investigated the relationship between ERD/ERS changes and motor function in ALS and created a simple strength stratification of our ALS group based on the strength of the investigated limb. The results show that beta power for both ERD and ERS, changes depending on the severity of muscle deficits in the tested limb (right arm), likely driven by the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies using varying techniques (single voxel or multivoxel) have consistently revealed reduced N-acetylaspartate (NAA, a chemical marker of neuronal integrity) in motor and extra-motor regions in ALS. Other metabolites of interest include myo-inositol (mIns, a glial marker), and the excitatory and inhibitory neurotransmitter system involving glutamate, glutamine, and GABA ( 159 ). Technological advances in MR hardware and spectral acquisition and editing methods have increased the ability to more readily resolve such metabolites.…”
Section: Molecular Imaging Of Disease-inherent Pathological Alteratio...mentioning
confidence: 99%
“…Prior work has reported differences in brain GABA levels across the healthy lifespan [1][2][3] , as well as in various psychiatric 4,5 and neurodegenerative conditions [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%